2020
DOI: 10.3390/ijerph17155287
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Environmental Regulation and Green Total Factor Productivity in China: An Empirical Study Based on the Panel Data of 177 Cities

Abstract: Promoting the coordinated development of industrialization and the environment is a goal pursued by all of the countries of the world. Strengthening environmental regulation (ER) and improving green total factor productivity (GTFP) are important means to achieving this goal. However, the relationship between ER and GTFP has been debated in the academic circles, which reflects the complexity of this issue. This paper empirically tested the relationship between ER and GTFP in China by using panel data and a syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…Equation (6) adds the secondary term of environmental regulation to Equation (5) to test whether there is a nonlinear relationship between environmental regulation and green total factor productivity [ 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. The results show that the primary term coefficient is positive, and the secondary term is negative, and both pass the 1% significance level test, indicating that environmental regulation can promote the development of regional green economy.…”
Section: Results From Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Equation (6) adds the secondary term of environmental regulation to Equation (5) to test whether there is a nonlinear relationship between environmental regulation and green total factor productivity [ 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. The results show that the primary term coefficient is positive, and the secondary term is negative, and both pass the 1% significance level test, indicating that environmental regulation can promote the development of regional green economy.…”
Section: Results From Analysismentioning
confidence: 99%
“…Environmental regulation can effectively promote industrial green transformation by improving green total factor productivity. Lei [ 37 ], Zhao [ 38 ] also found that environmental regulation has a nonlinear impact on green total factor productivity. The research results show that different types of environmental regulations have different effects on the green total factor productivity of different polluting industries, and the green total factor productivity of heavily polluting industries is in an inverted U shape [ 39 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Owing to the importance of green development of the marine economy, we examine the impact of environmental regulation on the GTFP of marine economy. Existing studies have discussed regional GTFP [32], industrial GTFP [33,34]. However, few existing studies have explored the GTFP of the marine economy.…”
Section: Introductionmentioning
confidence: 99%
“…In this situation, green total factor productivity (GTFP) has become the main driving force and quantitative standard for driving China's economic development [2]. In practice, scholars have conducted a series of discussions on the improvement paths of GTFP, focusing on government systems [3], technological development [4], foreign trade [5], and financial development [6]. Among them, the role of environmental regulation in the improvement of GTFP has aroused heated discussion in academic circles.…”
Section: Introductionmentioning
confidence: 99%